Jenseits von Textbeziehungen. Paul Celan bei Yoko Tawada: [Beyond textual relationships. Paul Celan in Yoko Tawada] (Studia theodisca, 2022)
This article aims at highlighting the metatextual relationships between the works of Yoko Tawada and Paul Celan. The analysis concentrates on Das Tor des Übersetzers oder Celan liest Japanisch and Paul Celan und der chinesische Engel and is carried out in the light of transtextual practices, starting from theoretical premises related to the act of reading (symptomatic reading – surface reading) and including the dimension of transculturality. The encounter between Tawada and Celan generates a multi-faceted textual space, in which texts from different cultures, having the German language as a common denominator, enter into dialogue with each other.